2018
DOI: 10.1007/s00268-018-4487-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Lymph Node Metastases of Papillary Thyroid Carcinoma, in the Central and Lateral Compartments, in Children and Adolescents: Predictive Factors

Abstract: Most predictors, unfortunately, are only identified post-operatively by histopathologic examination: Just a small part of them can be pre-operatively detected with a low-sensitivity neck ultrasonography. In PTC patients with pre-operative predictors, we suggest an accurate pre- and intra-operative evaluation of CC and/or LC to find suspicious lymph nodes. The presence of LNM in CC has an impact on disease/progression/relapse-free survival. We suggest performing RAI therapy and an accurate follow-up for pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 67 publications
6
37
2
1
Order By: Relevance
“…In many studies, the association between male and CLNM were signi cant [22]. However, Spinelli et al [23] reported no signi cant correlation. In our study, ratio of female /male ratio was 1:3, which was consistent with previous studies [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In many studies, the association between male and CLNM were signi cant [22]. However, Spinelli et al [23] reported no signi cant correlation. In our study, ratio of female /male ratio was 1:3, which was consistent with previous studies [2].…”
Section: Discussionmentioning
confidence: 98%
“…Our data revealed that patients aged <55 years were more prone to LNM and NMLNs >5 and ten-year age was an independent predictor for the low prevalence of LNM and NMLNs >5. However, Spinelli et al [23] retrospectively discussed the clinical characteristics of 132 children and adolescents with PTC and found that age was not related to LNM. These results vary from ours due to difference in the target population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment approach for this disease is changing. In recent years, prophylactic CCND has not been recommended for PTMC patients without LNM . The median risk of local‐regional lymph node recurrence varies markedly by clinical staging in patients with pathologically proven neck LNM, with recurrence rates of 2% (range 0%‐9%) in patients with an initial N0 stage vs 22% (range 10%‐42%) in those with initially positive lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, prophylactic CCND has not been recommended for PTMC patients without LNM. 8,[22][23][24][25] The median risk of local-regional lymph node recurrence varies markedly by clinical staging in patients with pathologically proven neck LNM, with recurrence rates of 2% (range 0%-9%) in patients with an initial N0 stage vs 22% (range 10%-42%) in those with initially positive lymph nodes. Furthermore, the median risk of recurrence in LNM patients varies markedly by the number of positive…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation